Trade and the Spillovers of Transnational Terrorism - José de Sousa; Daniel Mirza; Thierry Verdier (Swiss Journal of Economics and Statistics, 2009)
We examine the impact of transnational terrorism diffusion on security and international trade. To counter the diffusion of transnational terrorism, targeted governments implement security measures against countries where terror could potentially diffuse. Since security measures raise trade costs, we argue that countries, close enough to those from where terror originates, should experience negative spillovers on their trade. We find evidence for this hypothesis in our data. We show that the closer a country is to a source of terrorism, the higher the negative spillovers on its trade.
Keywords: F12; F13; 330; Terrorism; trade; security